Biologia reprodutiva e citogenética de espécies simpátricas de Croton L. (Euphorbiaceas) - Santos, Amanda de Souza (2016)
The Croton genus often presents itself in plant communities with several sympatric species without clear evidence of interspecific hybridization. Aiming to evaluate the existence of reproductive isolation barriers and potential hybridization between these species, it was evaluated different aspects of the reproductive biology of three sympatric species of Croton (C. heliotropiifolius, C. jacobinensis e C. urticifolius), in three different populations, by means of reproductive isolation mechanisms of pre-zygotic (flowering synchrony, floral biology and pollinators of each species), as post-zygotic (seed formation after controlled pollination experiments and cytogenetic analysis). We also analyzed the karyotypes of more 12 species of the genus Croton, surveying of all chromosome numbers previously known to the genus, and analyzed in a phylogenetic context in order to identify the ancestral basic number of the genus. The reproductive phenology of species varies among populations; however we observed a significant degree of synchrony floral species within populations. There are sharing of pollinators among them, being the most frequently: Apis sp., and Trigona sp., that visit flowers looking for nectar. They are self-compatible, with high fruit formation, no significant differences with regard to the formation of natural and intraspecific fruit. These results indicate weak pre-zygotic reproductive barriers for these sympatric species of Croton. Moreover, these species are inter-compatible with formation of interspecific fruits, suggesting the occurrence of an incomplete barrier post-zygotic reproductive isolation, allowing the formation of interspecific hybrids. The three species have chromosome number 2n = 20, with different patterns of heterochromatin. Karyotype differences in numbers and chromosomal structure usually constitute effective barriers to post-zygotic reproductive isolation. These results associated with the seed germination study in progress, suggest the need for further investigation in post-zygotic reproductive isolation barriers for these Croton species. Among the other species of the genus analyzed cytogenetically, most presented 2n = 20 except a population of Croton pulegioides (2n = 22) and C. limae (2n = ca.100). Five of the species analyzed had no previous records of chromosome counts: C. limae with 2n = ca.100, and C. rudolphianus, C. tricolor, C. adamantinus, and C. grewioides with 2n = 20. Most species presented two heterochromatic bands CMA+/DAPI– larger, located in the terminals of the short arms of a chromosome pair corresponding to RON. Whereas in species C. rudolphianus, C. urticifolius and C. sellowii, the RON was proximal. All species have distal regions of all chromosome arms (except the NORs), strongly stained with as DAPI. The analysis of molecular phylogeny combined with records of chromosome counts showed that the basic number x = 10 is the most likely for the genus. Although some species showed basic numbers different from x = 10, as C. xalapensis (x = 32), C. ruizianus (x = 8) and C. sarcopetalus (x = c.60), these numbers did not have significant values of Proportional Likelihoods to the ancestral basic number of the genus.